Peran Public Relations Himakom dalam Membangun Komunikasi Organisasi di Lingkungan kampus UMJ (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Public Relations (PR) plays a strategic role in building effective organizational communication, including within student organizations. The Communication Studies Student Association (Himakom) of Muhammadiyah University of Jakarta (UMJ), as an internal campus organization, requires a PR role to maintain internal relationships among members and external relationships with the academic community. This study aims to determine the role of Himakom UMJ Public Relations in building organizational communication on campus. The research method used was a qualitative method with a descriptive approach. Data collection techniques were conducted through literature studies and conceptual observations of student organization public relations activities. The results indicate that Himakom Public Relations plays a role as a communicator, information facilitator, organizational image builder, and liaison between the organization and internal and external publics. This role contributes to creating effective, harmonious, and sustainable organizational communication on the UMJ campus